2021
DOI: 10.1101/2021.01.20.427515
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deconvolving clinically relevant cellular immune crosstalk from bulk gene expression using CODEFACS and LIRICS

Abstract: The tumor microenvironment (TME) is a complex mixture of cell-types that interact with each other to affect tumor growth and clinical outcomes. To accelerate the discovery of such interactions, we developed CODEFACS (COnfident DEconvolution For All Cell Subsets), a deconvolution tool inferring cell-type-specific gene expression in each sample from bulk expression measurements, and LIRICS (LIgand Receptor Interactions between Cell Subsets), a supporting pipeline that analyzes the deconvolved gene expression fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…It is reported that the exhaustive molecular marker, PD-1, which is expressed on the surface of exhausted T cells, impaired the tumor-killing effects in tumor tissues [26,27]. Therefore, the immune checkpoint blocker PD-1 mAb is the most widely used reagent for anti-tumor immunotherapy in clinical practice [28][29][30]. However, prior to performing the PD-1 mAb therapy, positive detection of PD-1 is necessary [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the exhaustive molecular marker, PD-1, which is expressed on the surface of exhausted T cells, impaired the tumor-killing effects in tumor tissues [26,27]. Therefore, the immune checkpoint blocker PD-1 mAb is the most widely used reagent for anti-tumor immunotherapy in clinical practice [28][29][30]. However, prior to performing the PD-1 mAb therapy, positive detection of PD-1 is necessary [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, conducting cell abundance deconvolution prior to cell-cell interaction scoring can help normalize heterogeneous samples and hence measure genuine changes in cell-cell interaction instead of those driven by a shift in cell composition. Similar approaches have been used in bulk expression studies, 34 but, here again, the availability of single-cell RNA-seq could alleviate the need for such computational tricks and directly measure LR interaction from pure populations of cells as conducted by multiple methods recently published. [35][36][37] As mentioned above, however, single-cell gene expression data is not available for pure DCIS specimens, and approaches like ours are needed to overcome the resulting lack of data.…”
Section: Discussionmentioning
confidence: 99%
“…Second, using a precomputed estimates of cell abundance or cell-type-specific signature based on deconvolving cell-type-specific gene expression in each sample from bulk expression 44 of LUAD patients, patients with higher average expression of the unique signature (65 genes) identified in Siah1a/2 ablated macrophages were also found to have increased myeloid cells (CD14 + ) infiltration (Figure 7G). The TCGA dataset of the LUAD was also used to identify which of the 65 genes are associated with worse survival.…”
Section: Siah1a/2 Deletion In Macrophages Promotes a Pro-fibrotic Phe...mentioning
confidence: 99%